Analisis Faktor-faktor Risiko Kejadian Stunting pada Anak: Studi Pustaka - Zulaikha, Fatma; Fitriani; Wahyuni (STIKES Ngesti Waluyo, 2022)
Stunting is a condition that the toddlers fail to grow as a result of persistent malnutrition, causing them to become too small for their age. Stunting is a nutritional problem that impacts children's health and can even be fatal globally, not only in Indonesia. Researchers can discover the risk factors of stunting both in Indonesia and throughout the world by doing a literature study. In order to reduce the incidence of stunting in children and provide information about stunting management, this study will investigate the variables that lead to stunting in children. A literature study was conducted using a scientific article search engine to find and examine several studies about stunting in children. Several of the risk variables for stunting in children include anemia during pregnancy, a history of chronic disease while pregnant, a pregnant patient's BMI, and antenatal care history. Future health and cognitive development of children can be influenced by stunting. The findings of this study are supposed to spur more study on childhood stunting.